Efforts to Stop Prosecutions Based on the Regulation of the Prosecutors of the Republic of Indonesia Number 15 of 2020 Perspective of the Theory of Dignity Justice - Abraham Ethan Martupa Sahat Marune; Teguh Prasetyo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The regulation of termination of prosecution based on efforts to stop prosecution based on Perja Number 15 of 2020 is an embodiment of the concept of restorative justice as an effort to peacefully settle criminal cases outside the trial. Termination of prosecution with the condition that compensation to victims is included as a form of restorative justice because the restoration of conditions resulting from criminal acts that occurred is the main focus of case settlement and the result of the second study is an effort to stop prosecution based on Perja Number 15 of 2020 in terms of the perspective of the Dignified Justice Theory that in justice what Pancasila wants is dignified justice. As initiated by Teguh Prasetyo, justice refers to divine values and places humans as creatures of God who have basic rights and obligations that must be upheld. One of them that puts forward a dignified theory of justice is restorative justice in the termination of prosecution as stated in Perja Number 15 of 2020. In the author's opinion, the termination of prosecution with the concept of restorative justice needs to be prioritized considering that a case must also be seen from the side of justice and in this case the Prosecutor's Office can give an example that the prosecution is not carried out unilaterally, but sees it from the other side, namely by using one's conscience.